Measurement of Digital Literacy Index of High School Students or Equivalent in Bogor Regency - Magfirawaty, Magfirawaty; Syahral, Mohamad; Ogi, Dion; Lestari, Andriani Adi; Amelia, Fetty; Khairunnisa, Rizka; Arizal, Arizal; Nurwa, Agus Reza Aristiadi (Universitas Negeri Semarang, 2024)
The digitalization era is developing rapidly in Indonesia. The pandemic that occurred accelerated digital transformation in various fields. Various digital platforms were developed to support the continuity of education during the pandemic so that they could develop digital skills and improve the status of digital literacy in Indonesia. In addition to the positive impacts, there are also negative impacts from the development of digital transformation. The National Cyber and Crypto Polytechnic which focuses on information security is committed to encouraging increased digital skills and literacy in the surrounding community. Therefore, this time the National Cyber and Crypto Polytechnic located in Bogor Regency began to focus on developing digital skills and literacy among high school students or equivalent in Bogor Regency. The students' digital literacy status was first measured and then the right program or activity was determined to develop their digital skills and literacy. The digital literacy status was measured based on four pillars, Pillar 1 Digital Skill, Pillar 2 Digital Ethics, Pillar 3 Digital Safety, and Pillar 4 Digital Culture. Data collection was carried out by giving questionnaires to 276 high school students or equivalent who used the internet in Bogor Regency. Students give a score to each statement and then the score will be calculated as an average per pillar. The digital literacy index is obtained from the average score of all pillars. The digital literacy index result is 3.14 which is higher than the West Java digital literacy index of 2.78. In addition, pillar 2 Digital Ethic has the lowest score among the four pillars so that the next program is expected to aim to increase this score.